2021
DOI: 10.1093/jpepsy/jsab060
|View full text |Cite
|
Sign up to set email alerts
|

OUP accepted manuscript

Abstract: Objective Sweden is an international exception in its public health response to the COVID-19 pandemic, with a higher number of deaths, albeit not pediatric, compared with other Nordic countries. The objective of this study was to investigate what worries children and adolescents living in Sweden expressed in relation to the pandemic. Methods Using an anonymous web-survey, 1,047 children (4-12 years; N ¼ 717) and adolescents (13-18 years; N ¼ 330) responded to five background and four open-ended questions, one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…A population-based study conducted in Sweden between May and June 2020, at the height of the COVID-19 pandemic, reported around 40% of respondents had significant problems in one or more areas of their mental health, including depression, anxiety, or insomnia [ 17 ]. Another study showed that children and adolescents were also worried about the pandemic for themselves and their elderly relatives [ 36 ]. Interestingly, a Swedish study that used crowdsourced, online data and qualitative analysis found that the most salient population concerns during COVID-19 were centered on a range of social problems, including fear of general societal collapse and political disorder [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A population-based study conducted in Sweden between May and June 2020, at the height of the COVID-19 pandemic, reported around 40% of respondents had significant problems in one or more areas of their mental health, including depression, anxiety, or insomnia [ 17 ]. Another study showed that children and adolescents were also worried about the pandemic for themselves and their elderly relatives [ 36 ]. Interestingly, a Swedish study that used crowdsourced, online data and qualitative analysis found that the most salient population concerns during COVID-19 were centered on a range of social problems, including fear of general societal collapse and political disorder [ 37 ].…”
Section: Discussionmentioning
confidence: 99%